Microbiological characterization of post-eruption “snowblower” vents at Axial Seamount, Juan de Fuca Ridge - Meyer, Julie L.; Akerman, Nancy H.; Proskurowski, Giora; Huber, Julie A. (Frontiers in Microbiology, 2013)
Microbial processes within the subseafloor can be examined during the ephemeral and uncommonly observed phenomena known as snowblower venting. Snowblowers are characterized by the large quantity of white floc that is expelled from the seafloor following mid-ocean ridge eruptions. During these eruptions, rapidly cooling lava entrains seawater and hydrothermal fluids enriched in geochemical reactants, creating a natural bioreactor that supports a subseafloor microbial “bloom.” Previous studies hypothesized that the eruption-associated floc is made by sulfide-oxidizing bacteria; however, the microbes involved were never identified. Here we present the first molecular analysis combined with microscopy of microbial communities in snowblower vents from samples collected shortly after the 2011 eruption at Axial Seamount, an active volcano on the Juan de Fuca Ridge. We obtained fluid samples and white flocculent material from active snowblower vents as well as orange flocculent material found on top of newly formed lava flows. Both flocculent types revealed diverse cell types and particulates when examined by phase contrast and scanning electron microscopy. Distinct archaeal and bacterial communities were detected in each sample type through Illumina tag sequencing of 16S rRNA genes and through sequencing of the sulfide oxidation gene, soxB. In fluids and white floc, the dominant bacteria were sulfur-oxidizing Epsilonproteobacteria and the dominant archaea were thermophilic Methanococcales. In contrast, the dominant organisms in the orange floc were Gammaproteobacteria and Thaumarchaeota Marine Group I. In all samples, bacteria greatly outnumbered archaea. The presence of anaerobic methanogens and microaerobic Epsilonproteobacteria in snowblower communities provides evidence that these blooms are seeded by subseafloor microbes, rather than from microbes in bottom seawater. These eruptive events thus provide a unique opportunity to observe subseafloor microbial communitie